Randomised clinical trial: alginate (Gaviscon Advance) vs. placebo as add‐on therapy in reflux patients with inadequate response to a once daily proton pump inhibitor. Issue 8 (22nd February 2016) - Reimer, C.; Lødrup, A. B.; Smith, G.; Wilkinson, J.; Bytzer, P.
Summary: Background: Many reflux patients remain symptomatic on a standard dose of proton pump inhibitor (PPI). Alginates decrease the number of reflux events by forming a raft on top of the stomach content and thus offer a supplemental mechanism of action to acid suppression. Aim: To assess the efficacy of an alginate (Gaviscon Advance, Reckitt Benckiser, Slough, UK) on reflux symptoms in patients with persistent symptoms despite once daily PPI. Methods: This was a multicentre, randomised, placebo‐controlled, 7‐day double‐blind trial preceded by a 7‐day run‐in period. Reflux symptoms were assessed using the Heartburn Reflux Dyspepsia Questionnaire (HRDQ). Based on symptom score during run‐in, eligible patients were randomised to Gaviscon Advance 10 mL four times a day or placebo in addition to a once daily PPI. The primary endpoint was change in HRDQ score post‐treatment compared to baseline. Results: One hundred and thirty‐six patients were randomised. Change in HRDQ reflux score was significantly greater for Gaviscon Advance (mean: −5.0, s.d.: 4.7) than for placebo (mean: −3.5, s.d.: 5.5) with an LS mean difference of 1.6 [95% CI −3.1 to −0.1], P = 0.03. A decrease in the mean (s.d.) number of nights with symptoms was observed from 3.6 (2.8) to 3.0 (3.0) in the placebo group and from 3.9 (2.8) to 2.2 (2.7) for the Gaviscon Advance group. This reduction was significantly greater in the Gaviscon Advance group than in the placebo group [LS mean difference = −0.9, 95% CI (−1.6 to −0.2), P < 0.01]. Conclusion: In patients with residual reflux symptoms despite PPI treatment, adding an alginate offers additional decrease in the burden of reflux symptoms (EudraCT/IND Number: 2011‐005486‐21).